2020
DOI: 10.1002/bse.2500
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term economic consequences of corporate environmental responsibility: Evidence from heavily polluting listed companies in China

Abstract: In this study, we aim to investigate the long‐term economic consequences of corporate environmental responsibility (CER) by companies from the perspective of earnings persistence and investors' response. Based on firm‐level data of 1,010 heavily polluting listed companies in China, the empirical results are as follows. First, the CER of China's heavily polluting listed companies has significantly improved their earnings persistence, that is, earnings quality. Second, the positive long‐term economic effect of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 60 publications
(102 reference statements)
3
51
0
Order By: Relevance
“…A strand of studies has shown that being environmentally responsible positively affects firm performance [32][33][34][35][36][37][38][39][40][41][42][43][44], and innovation [45]. For instance, Deng and Cheng (2019) [41] find that CER and stock market performance has a positive correlation.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…A strand of studies has shown that being environmentally responsible positively affects firm performance [32][33][34][35][36][37][38][39][40][41][42][43][44], and innovation [45]. For instance, Deng and Cheng (2019) [41] find that CER and stock market performance has a positive correlation.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Text content analysis is a very popular method of collecting environmental information from relevant reports. Given that China's listed companies are all required to disclose their annual social responsibility reports, this study adopts the method of text analysis to measure the quality of enterprise EID (Chen et al, 2018;Xu et al, 2020). Specifically, the quality of corporate's environmental information disclosure is measured by the number of items of environmental information disclosed in the corporate social responsibility report.…”
Section: Measurement Of Eidmentioning
confidence: 99%
“…EID transfers the legitimacy of enterprises to the public, reduces the investment risk of external shareholders, and ultimately improves the financing ability of enterprises (Dhaliwal et al, 2011). Moreover, EID makes it easier for polluters to obtain green credit and reduce the cost of credit (Liu and Anbumozhi, 2009;Xu et al, 2020). Therefore, EID can further improve the financing ability of polluting enterprises (Wu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental regulation, when improving environmental performance, inevitably affects activities such as resource reallocation, capital investment and technological innovation in the production process of rms (Albrizio et al 2017), which in turn affects enterprises' TFP. On the one hand, enterprises that comply with environmental regulation are more likely to get preferential measures such as nance, tax, price and government procurement (Xu et al 2020), which will provide essential guarantee for the growth of TFP. On the other hand, environmental regulation provides necessary external conditions for enterprises to improve production e ciency.…”
Section: Research Hypothesesmentioning
confidence: 99%